Development of a full ocean depth hydraulic manipulator with heavy-duty capacity - Ruan, Dongrui; Chen, Jiawang; Peng, Xiaoqing; Ai, Jingkun (Frontiers in Marine Science, 2024)
To enhance the performance of underwater grasping tasks during marine exploration, we developed a heavy-duty capacity full ocean depth hydraulic manipulator. The manipulator's overall system design comprises the mechanical structure part and the electric control system part. The master arm controls the slave arm by sending control signals to the controller and valve box. The structural design of the elbow and wrist joints has been designed to improve the underwater working performance and activity space of the manipulator. Laboratory tests confirmed the manipulator's excellent response consistency and tracking ability across a large range of movement. Finally, the manned submersible Fendouzhe carried the manipulator for sea trials in the Mariana Trench, with results indicating an excellent capacity for successfully completing tasks.